2010
DOI: 10.1111/j.1365-2796.2009.02146.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a high‐dose nitrate strategy on cardiac stress in acute heart failure: a pilot study

Abstract: Abstract. Breidthardt T, Noveanu M, Potocki M, Reichlin T, Egli P, Hartwiger S, Socrates T, Gayat E, Christ M, Mebazaa A, Mueller C (University Hospital, Basel, Switzerland, University Paris, Paris, France, and Klinikum Nürnberg, Nürnberg, Germany). Impact of a high-dose nitrate strategy on cardiac stress in acute heart failure: a pilot study. J Intern Med 2010; 267: 322-330.Background. Intravenous nitrate therapy has been shown to improve short-term outcome of acute heart failure patients treated in the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Marginal benefits and mixed outcomes are common findings among the studies that have been performed [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Marginal benefits and mixed outcomes are common findings among the studies that have been performed [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Levy et al found that patients who received high‐dose nitroglycerin experienced decreased need for intubation, noninvasive mechanical ventilation, and ICU admission 14. Reduced need for mechanical ventilation was also found by Cotter et al,24 although this finding was not observed to be significant by Breidthardt et al 25. However, despite the above, mortality is a clinically important outcome, which was not demonstrably improved in any of the aforementioned smaller studies and also in our present evaluation.…”
Section: Discussionmentioning
confidence: 88%
“…However, the study was terminated prematurely and a total of 2 deaths occurred during the study, limiting its inference in relation to survival benefit. Lastly, Breidthardt et al demonstrated in 128 patients that high‐dose nitrates accelerated improvement in serial brain natriuretic peptide measurements, but they found no effect on clinical outcomes including mortality, length of stay, or 90‐day rehospitalization rates 25. The caveat in interpretation of the aforementioned trial is that there were only 20 deaths in the entire study 25.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Breidthardt showed that sublingual and transdermal nitrates had an improving effect on the mortality in patients with acute HF. Breidthardt showed that high-dose sublingual or transdermal nitrate on top of standard HF therapy was safe and accelerated cardiac recovery (20). In another study, it was found that IV nitrate improved cardiac function in patients with acute HF due to severe aortic stenosis (21), in which vasodilators are generally thought to be contraindicated.…”
Section: Discussionmentioning
confidence: 92%